If you say so: A mixed-method study of hospital mergers and quality of care. Issue 1 (9th January 2022) - Westra, Daan; Angeli, Federica; Kemp, Ron; Batterink, Maarten; Reitsma, Jan
Abstract : Supplemental digital content is available in the text. Abstract : Background: Despite a lack of supporting evidence, hospitals continue to merge in pursuit of quality improvements. Purpose: We seek to develop a more thorough understanding of the quality effects of hospital mergers by integrating various theoretical perspectives using a mixed-methods design. Methodology: Quantitatively, we tested the quality effect of all consummated hospital mergers in the Netherlands between 2008 and 2014 on 15 quality indicators (with 82 measurements at hospital, department, and disease levels) using a difference-in-difference approach with Bonferroni correction. Qualitatively, we conducted three comparative case studies to examine how hospital executives, managers, and medical professionals perceive the quality impact of hospital mergers. Results: Our quantitative results reveal few significant effects of hospital mergers on quality of care at all levels. After applying Bonferroni correction, two quality indicators are negatively associated with hospital mergers. However, the qualitative results indicate that hospital staff have positive perceptions of the mergers' quality implications, resulting from scale and shock effects. Conclusion: The perceptions of hospital staff regarding mergers diametrically oppose their measurable effects. However, the operationalization of quality by hospital staff members differs considerably from the way it is quantitatively measured. The positive perceptions of hospital staff toward mergers could further contribute to the institutionalization of mergers as a quality improvement strategy. Practice Implications: Hospital managers seeking measurable quality improvements should be wary of merging, despite potential positive perceptions toward it within the organization. In case they do decide to merge, mitigating difficulties in the postmerger integration processes seem most pertinent to achieve measurable effects.